JUANA PAULA MANSO (1819-1875) THE UNDENIABLE FEMININE PRESENCE IN THE ARGENTINIAN EDUCATION AND CULTURE OF THE XIXTH CENTURY, WITH AMERICAN RENOWN (2012)
This analysis and reflection work about the life, personality and the Juana Paula Manson’s works, offers the possibility to know chronologically the most transcendent milestones of her life, her exiles and her productions. To understand the importance of the contributions of this writer, journalist and also an awkward and coherent teacher of the nineteenth century, there were analyzed her works referred to the education, to the defense of the woman as for her capacities and rights. Also the letters sent to her friends prominent figures of the epoch have been taken into consideration, especially, those ones to Domingo Faustino Sarmiento and to Mary Mann, the last documents showed, with an intimate tone, that woman in her fights, often without fruits. The education in the kindergartens and in the Primary level constitutes the axle of her studies and her educational professional performance, thus she wrote pedagogic articles, in which she analyzes and she advises on all the aspects referred to the education, since the political lines until the didactic and psychological considerations to develop the education on scientific bases. The author demonstrates to have a clear historical conscience of her time, for this reason, through her works it is possible to establish the relations of the historical, cultural and social context, among Argentina, America and Europe.